Aplikasi Monitoring Penderita Kardiovaskular dan Obesitas Berbasis Mobile Internet of Things (MIoT) - Muhamad Bahrul Ulum; Nizirwan Anwar; Riya Widayanti; Alivia Yulfitri; Hendra Bratanata (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2020)
According to the World Health Organization (WHO), coronary heart disease is the biggest cause of death in Indonesia. In 2016, the death rate from heart disease was 122 people per 100,000 population. This figure is higher than other causes, such as stroke, tuberculosis, and diabetes. The number is increasing every year due to changes in lifestyle of Indonesian people who like to eat high-fat foods and lifestyle factors that affect the risk of cardiovascular disease, including lack of physical activity, smoking, unhealthy diet, and alcohol consumption habits. This study aims to monitor the heart rate of cardiovascular sufferers with the mobile internet of things (MIoT) approach. Using the ESP8266 Wifi module for communication to the database server and heart rate sensor to detect heart rate then convert it to Bit per Minute (BPM). Every patient with cardiovascular disease can be monitored using a sensor connected to a smartphone to record any changes that occur. The research method consists of several stages, namely: Prepare, Plan, Design, Implement, Operate and Optimize (PPDIOO). The results obtained in the form of a aplication heart rate monitoring for patients with cardiovascular for healthcare services.